Acquired Pellicle and Biofilm Engineering by Rinsing with Hemoglobin Solution - Araujo, Tamara T.; Carvalho, Thamyris S.; Dionizio, Aline; Rodrigues, Chelsea Maria V.B.F.; Henrique-Silva, Flavio; Chiaratti, Marcos; Santos, Angélica; Alves, Lindomar; Ferro, Milene [UNESP]; Buzalaf, Marília A.R. (Karger Publishers, 2024)
Introduction: The identification of acid-resistant proteins, including hemoglobin (Hb), within the acquired enamel pellicle (AEP) led to the proposition of the acquired pellicle engineeringconcept, which involves the modification of the AEP by incorporating specific proteins, presenting a novel strategy to prevent dental demineralization. Objective: Combining in vivo and in vitro proof-of-concept protocols, we sought to reveal the impact of AEP engineering with Hb protein on the biofilm microbiome and enamel demineralization. Methods: In the in vivo studies, 10 volunteers, in 2 independent experiments, rinsed (10 mL,1 min) with deionized water-negative control or 1.0mg/mL Hb. The AEP and biofilm formed along 2 or 3 h, respectively, were collected. AEP was analyzed by quantitative shotgun-label-free proteomics and biofilm by 16SrRNA next-generation sequencing (NGS). In in vitro study, a microcosm biofilm protocol was employed. Seventy-two bovine enamel specimens were treated with (1) phosphatebuffered solution (PBS), (2) 0.12% chlorhexidine, (3) 500 ppm NaF, (4) 1.0mg/mL Hb, (5) 2.0mg/mL Hb, and (6) 4.0mg/mL Hb. The biofilm was cultivated for 5 days. Resazurin, colony forming units (CFU), and transversal microradiography were performed. Results: Proteomics and NGS analysis revealed that Hb increased proteinswith antioxidant, antimicrobial, acid-resistance, hydroxyapatite-affinity, calcium-binding properties and showed a reduction in oral pathogenic bacteria. In vitro experiments demonstrated that the lowest Hb concentration was the most effective in reducing bacterial activity, CFU, and enamel demineralization compared to PBS. Conclusion: These findings suggest that Hb could be incorporated into anticaries dental products to modify the oral microbiome and control caries, highlighting its potential for AEP and biofilm microbiome engineering.
Keywords: Acquired enamel pellicle; Biofilm; Demineralization; Dental caries; Hemoglobin; Microbiome